Functional Role of Frequency in Word-Formation Processes: A System Theoretical Approach. Issue 1 (2nd January 2020) - Uglanova, Inna
ABSTRACT: Three experimental models are reported in which verb-formation processes are used to investigate the effect of frequency on language structure. The first model examined the impact of frequency on length of a language unit. Only the smoothed data for the prototypical verb formation confirmed the hypothesis. The second model tested the dependency of frequency on the depth of a word-formation structure. Good-fitting results were found for all main verb-formation structures. The third model aimed to study the influence of frequency on productivity (number of derivatives). The results of smoothing data showed that the more frequently a unit is used, the more derivatives it has. The outcomes allow clarifying some aspects of functioning of frequency in the synergetic mechanisms of language. In particular, it was shown that the observed frequency oscillation could be considered as a dialogue between the system and its environment.